Contraction operators, defect functions, and scattering theory - Boiko, C. C.; Dubovoi, V. K.; Kirstein, B.; Fritzsche, B. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study functions that describe scattering through inner channels of a system (defect functions) and the corresponding contraction operators.